Microelectronic circuit design for energy harvesting systems - Emilio, Maurizio Di Paolo (Springer, 2017)
This book describes the design of microelectronic circuits for energy harvesting, broadband energy conversion, new methods and technologies for energy conversion. The author also discusses the design of power management circuits and the implementation of voltage regulators. Coverage includes advanced methods in low and high power electronics, as well as principles of micro-scale design based on piezoelectric, electromagnetic and thermoelectric technologies with control and conditioning circuit design. Provides a single-source reference to energy harvesting and its applications; Serves as a practical guide to microelectronics design for energy harvesting, with application to mobile power supplies; Enables readers to develop energy harvesting systems for wearable/mobile electronics.